Ratio Decidendi of Judge's Decision in Marriage Annulment Case: Antinomy between Justice and Legal Certainty in Depok Religious Court - Uu Lukmanul Hakim; Muhammad Nur Hussein Wahyudin; Charles Sugiarto Sitorus; Yeni Nuraeni; Lasmin Alfies Sihombing (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
In this article, the author will analyze the ratio decidendi of the judge's decision in the case of marriage annulment which shows the existence of an antinomy between Justice and Legal Certainty based on decision Number 3617/Pdt.G/2021PA. Dpk, decision Number 36/Pdt.G/2022/PTA. Bdg and decision Number 811 K/Ag/2022. The results of the study show that in marriage annulment cases, the panel of judges of first instance, the panel of appellate judges and the panel of cassation have different ratios decidendi in their legal considerations, so that from the three decisions there is an antinomy (contradiction) between justice and certainty. The panel of judges of the first instance, which considers one legal fact, but ignores other legal facts, causes the lack of legal certainty. The Appellate Panel considered that Article 27 paragraph (3) of Law Number 1 of 1974 had fulfilled legal certainty, but ignored other legal facts so as to ignore the values of justice. On the other hand, the Cassation Panel in its ratio decidendi decision has considered various legal facts, both formally and materially, so that it has considered two legal ideals, namely justice and legal certainty in a proportionate and balanced manner.